2021
DOI: 10.3390/ma14154317
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Ti-Based Intermetallic Alloys: A Review and Conceptualization of a Next-Generation Machine

Abstract: TiAl-based intermetallic alloys have come to the fore as the preferred alloys for high-temperature applications. Conventional methods (casting, forging, sheet forming, extrusion, etc.) have been applied to produce TiAl intermetallic alloys. However, the inherent limitations of conventional methods do not permit the production of the TiAl alloys with intricate geometries. Additive manufacturing technologies such as electron beam melting (EBM) and laser powder bed fusion (LPBF), were used to produce TiAl alloys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Despite the well-celebrated advantages offered by the LPBF process, it is well documented that the surface quality of LPBF products is one of its main drawbacks, limiting the technology from widespread industrial applications [62]. Currently, the LPBF process is mainly used to produce highvalue products for biomedical and engineering applications in the aerospace and automobile industries [16]. These industries require a specific surface quality for a specific application.…”
Section: Surface Quality Of the Ti10mo Alloy Matrix Layersmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the well-celebrated advantages offered by the LPBF process, it is well documented that the surface quality of LPBF products is one of its main drawbacks, limiting the technology from widespread industrial applications [62]. Currently, the LPBF process is mainly used to produce highvalue products for biomedical and engineering applications in the aerospace and automobile industries [16]. These industries require a specific surface quality for a specific application.…”
Section: Surface Quality Of the Ti10mo Alloy Matrix Layersmentioning
confidence: 99%
“…Despite these confirmations of low elasticity, non-toxicity, preferential biomechanical and biochemical properties of the Ti-Mo alloy, the processing of the Ti10Mo alloy via the conventional methods (casting, forging, sheet forming, extrusion, etc.) was very difficult [16,17]. This is because Mo is a refractory metal with a high melting point [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advantages of low density, high melting point, and high specific strength, TiAl alloy has great potential in the field of aerospace. Numerous scholars have carried out studies on the processing methods and mechanical properties of TiAl-based alloys [ 1 , 2 , 3 , 4 ]. Cheng et al [ 5 ] studied the high-temperature deformation properties of a TiAl-based alloy and found that super-plasticity occurs—that is, when the temperature reaches 1000 ℃, the deformation mechanism of this alloy converted from the original dislocation slip and twinning to a grain boundary sliding mode.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of Nickel-Titanium alloy, both superelasticity and shape memory effect are used for stents to decrease their volume during placement with subsequent extension under temperature influence and to impart a constant load on the walls of the vessel respectively. Furthermore, for intermetallic alloys such as NiTi [ 22 , 23 , 24 , 25 ], TiAl [ 26 , 27 ], NiAl [ 28 ], etc. application of LPBF technology can remarkably reduce the cost of the parts with complex geometries due to the poor machining of the material associated with high ductility accompanied by a strongly pronounced strain hardening effect [ 29 ].…”
Section: Introductionmentioning
confidence: 99%